Design analysis of web-based employee information system in office of technical implementation unit of education department - Ayshwarya B.; Yansyah A.; Nguyen P.T.; Shankar K.; Hashim W.; Abadi S.; Odarich I.N.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
KUPT Education Agency of Gunung Alip Sub-District is institution that handles education of elementary/kindergarten level in Gunung Alip Sub-District and all employees in KUPT Education Agency.KUPT Education Agency of Gunung Alip Sub-District in maintaining administration manually.Therefore Information System is needed to can help manage administration, especially personnel, quickly and easily.In making this information system the author used the waterfall method, Website programming.The resulting information system is expected to be used to manage employee data at the KUPT Education Office in Gunung Alip Sub-District. 2019, Blue Eyes Intelligence Engineering and Sciences Publication. All rights reserved.